A new species of Pristimantis (Anura: Strabomantidae) from white-sand forests of central Amazonia, Brazil - Alexander Tamanini Mônico; Miquéias Ferrão; Jiří Moravec; Antoine Fouquet; Albertina P. Lima (PeerJ, 2023)
The white-sand ecosystems in the Solimões-Negro Interfluve are among the less studied in Amazonia. Recent herpetological surveys conducted west of Manaus, Brazil (central Amazonia) indicate that white-sand forests host a unique anuran fauna comprising habitat specialized and endemic species. In the present study we describe a new species of rain frog belonging to the Pristimantis unistrigatus species group from the white-sand forest locally called “campinarana” (thin-trunked forests with canopy height below 20 m). The new species is phylogenetically close to rain frogs from western Amazonian lowlands (P. delius, P. librarius, P. matidiktyo and P. ockendeni). It differs from its closest relatives mainly by its size (male SVL of 17.3–20.1 mm, n = 16; female SVL of 23.2–26.5 mm, n = 6), presence of tympanum, tarsal tubercles and dentigerous processes of vomers, its translucent groin without bright colored blotches or marks, and by its advertisement call (composed of 5–10 notes, call duration of 550–1,061 ms, dominant frequency of 3,295–3,919 Hz). Like other anuran species recently discovered in the white-sand forests west of Manaus, the new species seems to be restricted to this peculiar ecosystem.